Gender-Based Violence in Muslim Families: A Quranic Analysis of Power Relations and Victim Protection - Hasan Basmaci; Necati Koca; Irem Yilmez; Ahmed Olgun; Aytan Eynizada (Arba: Jurnal Studi Keislaman, 2026)
This article begins with the gap between the normative construction of the Quran, which emphasizes justice, reciprocity, and moral responsibility in family relations, and the empirical reality of persistent gender-based violence in Muslim families. This gap is exacerbated by the tendency of reading religious texts to place power relations hierarchically, thereby normalizing gender inequality and weakening the position of victims. This study aims specifically to analyze the concept of power relations in the family according to the Quran and to identify the ethical principles of the Quran that serve as a normative basis for protecting victims of gender-based violence. The study uses a qualitative method based on a literature review, with a thematic-critical interpretation and contextual analysis, examining key verses on family leadership, husband-wife relations, trust, justice, and the protection of vulnerable parties through the ethical framework of the Quran, with a focus on maqāṣid al-Sharīʻah and human dignity. The results of this study indicate, first, that the concept of qiwāmah and family authority in the Quran is strictly limited by the principles of justice, non-exploitation, and moral responsibility, rather than by the legitimacy of domination. Second, the Quran normatively rejects all forms of violence by positioning power relations as an ethical mandate that must safeguard the safety, honor, and rights of the more vulnerable. Third, gender-based violence is a distortion of the Quran’s normative purpose and arises from a textual-hierarchical reading that ignores the context and ethical orientation of the verses. In conclusion, the Quran provides a firm ethical-theological framework for rejecting the normalization of violence and siding with victims, with important implications for the development of gender-sensitive and integrative Quranic interpretations in responding to the problem of contemporary family violence.